BIOCHEMICAL AND IMMUNOLOGICAL ASSESSMENT OF ANTITRYPANOSOMAL EFFECT OF NIGELLA SATIVA IN WEST AFRICAN DWARF BUCKS INOCULATED WITH TRYPANOSOMA BRUCEI - Akintunde, Olatunde O.; Nyenti, Besong P.; Ameen, Saliu Akanni; Rom-Kalilu, Fiwasade A.; Biobaku, K. Talha; Rafiu, Kadir A.; Ambali, M. Hauwa (FUDMA Journal of Sciences, 2025)
African trypanosomosis remains a tropical disease with effects on livestock productivity and agricultural economies. Trypanosoma-brucei infection triggers prompt antigenic variation, and immunomodulatory responses. This study aimed at biochemical and immunological assessment of the antitrypanosomal effects of Nigella-sativa oil on T.brucei-West-African-Dwarf- (WAD) bucks. Sixteen (16) relatively healthy WAD bucks (11.4–12.4 kg, were randomised into four groups (n = 4): uninfected-control; infected + Nigella-sativa oil (40 µL/kg IV on days 22 & 26); infected + diminazene aceturate ; and infected-untreated. Infection was established by jugular-inoculation of 1 mL suspension containing 2×108 T. brucei/ml. Parasitaemia was monitored weekly. Serum samples at peak infection (day 21) and post-treatment (day 35) were assayed for catalase (CAT), superoxide-dismutase (SOD), reduced glutathione (GSH), malondialdehyde (MDA), interleukin-6 (IL-6), interleukin-10 (IL-10), and cardiac-troponin I (cTnI). Nigella-sativa oil decreased peak parasitaemia from 3.2 × 108 to 1.2 × 107 trypanosomes/ml, attaining 50 % survival; diminazene-aceturate cleared parasites by week-5 with 75 % survival. The disease caused marked decrease in CAT, SOD, and GSH with increased MDA, IL-6, IL-10, and cTnI (p < 0.05). Both treatments lowered MDA and raised CAT and SOD (p < 0.05), but only diminazene restored GSH. Nigella-sativa failed to normalise cytokines or cTnI, whereas diminazene returned IL-6, IL-10, and cTnI toward baseline. Intravenous Nigella-sativa oil shows mild antitrypanosomal effect and partial antioxidant enhancement, but cannot fully clear infection or stop myocardial injury. If integrated with diminazene-aceturate, Nigella-sativa might aid as supportive therapy to facilitate parasite clearance and alleviate oxidative and inflammatory damage.